1985
DOI: 10.3758/bf03329832
|View full text |Cite
|
Sign up to set email alerts
|

The effect of music on eating behavior

Abstract: The effects of music tempo on number of bites per minute and total time of meal were studied. Eleven subjects unknowingly participated in the study. Three music conditions were used: fast tempo, slow tempo, and no music. A significant increase in the number of bites per minute was found; the effect was largest for fast-tempo music, which suggests arousal as a possible mediator. No difference was found in total time of meal. A questionnaire revealed no evidence that subjects were aware of the music.In the past,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
69
1
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(80 citation statements)
references
References 6 publications
7
69
1
2
Order By: Relevance
“…This finding is in line with a number of studies all of which have demonstrated that fast tempo music increases an individual's pace of an activity, whereas slower tempos reduce it (Milliman 1982, 1986, Roballey et al 1985, McElrea and Standing 1992, and Caldwell and Hibbert 1999. The finding may also be indicative of the notion that music with a quick tempo being arousing, and that noise may improve performance on a task.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is in line with a number of studies all of which have demonstrated that fast tempo music increases an individual's pace of an activity, whereas slower tempos reduce it (Milliman 1982, 1986, Roballey et al 1985, McElrea and Standing 1992, and Caldwell and Hibbert 1999. The finding may also be indicative of the notion that music with a quick tempo being arousing, and that noise may improve performance on a task.…”
Section: Discussionsupporting
confidence: 89%
“…Studies manipulating the tempo of music have found that faster music leads to more positive judgements of advertisements (Stout and Leckenby 1988), enhances effects on the performance of tasks (e.g. Tenenbaum et al 2004), leads to faster movement (Milliman 1982), faster dining (Caldwell and Hibbert 1999;McElrea and Standing 1992;Milliman 1986;Roballey et al 1985), and higher arousal levels (Kellaris and Kent 1993). Slow music has the opposite effects resulting in more relaxing, solemn adjectives being used when participants described it.…”
mentioning
confidence: 95%
“…Many researchers have investigated whether the rate at which people consume food and drink, as well as the total amount consumed, can be influenced by the characteristics of the background music (e.g., Bach and Schaefer 1979;Drews et al 1992;Guéguen et al 2004;McCarron and Tierney 1989;Ragneskog et al 1996;Roballey et al 1985). For example, McCarron and Tierney conducted a study in an experimental environment in which they reported an increase in the consumption of soft drinks when background music was amplified (from no background music to music played at 70 or 90 dB).…”
Section: Auditory Contributions To the Rate At Which People Consume Fmentioning
confidence: 99%
“…Similarly, McElrea and Standing (1992) demonstrated that drinking time decreased significantly when people listened to fast tempo music (132 bpm) than when they listened to the same music played at a slower rate (54 bpm). Moreover, increasing the tempo of background music has been shown to lead to a significant increase in the rate at which people eat, when measured in terms of the number of bites of food per minute (Roballey et al 1985).…”
Section: Auditory Contributions To the Rate At Which People Consume Fmentioning
confidence: 99%
“…But music can also act on the "crowd management", by influencing the time spent ANALYZING THE IMPACT OF SENSORY MARKETING ON CONSUMERS 281 inside by the customer. For example, according to two studies from Roballey et al (1985) and Milliman (1986), a fast-tempo music will push the customer to leave earlier. On the other hand, a slow music played at low volume will increase the time and the money spent inside.…”
mentioning
confidence: 99%